2010
DOI: 10.4161/psb.5.12.13775
|View full text |Cite
|
Sign up to set email alerts
|

Induction of alternative respiratory pathway involves nitric oxide, hydrogen peroxide and ethylene under salt stress

Abstract: Respiration plays a pivotal role in the metabolism of plants by providing adequate energy and carbon sources to drive the cellular metabolism and transport processes. In addition to the cytochrome pathway (CP), plant mitochondria have a cyanide-resistant respiration electron transport pathway, the alternative respiratory pathway (AP). Alternative oxidase (AOX) is used as the terminal oxidase in the AP and located in the inner membrane of mitochondria. It is well known that the AP plays an important role in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…H 2 O 2 , as a signaling molecule, is involved in multiple plant response to environmental stresses (Neill et al, 2003 ; Mittler et al, 2004 ; Zhang et al, 2007 ; Wang et al, 2010b ). Feng et al ( 2008 ) and Wang et al ( 2010a ) also confirmed H 2 O 2 could induce AP and AOX1 expression under chilling and salinity conditions. Recently, we studied whether H 2 O 2 is involved in the BRs-induced AOX capacity (Deng et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
“…H 2 O 2 , as a signaling molecule, is involved in multiple plant response to environmental stresses (Neill et al, 2003 ; Mittler et al, 2004 ; Zhang et al, 2007 ; Wang et al, 2010b ). Feng et al ( 2008 ) and Wang et al ( 2010a ) also confirmed H 2 O 2 could induce AP and AOX1 expression under chilling and salinity conditions. Recently, we studied whether H 2 O 2 is involved in the BRs-induced AOX capacity (Deng et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
“…Some previous studies proposed that the beneficial effect of CN on germination might involve the CN-insensitive pathway (Upadhyaya, Naylor & Simpson 1983;Oracz et al 2008). In addition, it has been recently demonstrated that ethylene and ROS might be involved in the stress-induced increase of the alternative pathway (Mittler 2002;Juszczuk & Rychter 2003;Ederli et al 2006;Wang, Huang & Bi 2010). Therefore, we hypothesize that CN might be involved in ethylene-induced alternative pathway under environmental stress.…”
Section: Introductionmentioning
confidence: 81%
“…AOX expression in response to various stresses has been shown independently to be mediated through ET signaling. Salt, ozone, metal, and pathogen induction of AOX was abolished in mutants of ETHYLENE RECEPTOR1 (ETR1) and/or EIN2 proteins that act upstream of EIN3/EIL1 in ET signal transduction (Simons et al, 1999;Tuominen et al, 2004;Wang et al, 2010;Keunen et al, 2015). It is unclear how the AOX transcription is regulated downstream from the ET signaling pathway, but dysfunctional MYC2 due to the absence of the functional MYB29 in the rao7 mutants could derepress EIN3/EIL1 and activate downstream ET transcriptional responses.…”
Section: Myb29 Interacts With Et Signaling Through Erf Tfsmentioning
confidence: 99%